Feto-maternal outcomes following labor induction at a tertiary care center - Pandit, Upendra; Sharma, Basant; Joshi, Rakshya; Chaudhari, Julli; Singh, Prekshya; Sharma, Asmita (Journal of Chitwan Medical College, 2020)
Background: Labor induction is one of the most common Obstetrics interventions worldwide. It has got significant risks and benefits. Careful selection of cases for induction improves the fetomaternal outcomes. So, the study was designed to assess the fetomaternal outcome and factors associated with mode of delivery following the induction of labor. Methods: It was a descriptive observational study conducted in the department of Obstetrics and Gynecology from July 17, 2018, to July 16, 2019. The study comprised of 264 mothers admitted in the labor ward subjected to labor induction as clinical management of labor and delivery. Data analyzed with chi-square test and one-way analysis of variance (ANOVA) wherever appropriate. Results: Of 2950 deliveries, the induction rate was 8.94%. Out of them, 264 mothers undergone labor induction. A caesarean was the highly associated mode of deliveries 168(63.63%) due to induction failure 94(55.97%) followed by fetal distress 37(22%). The mean birth weight of neonates was 3.09±0.41 kg. Apgar score in one minute and hospital stay showed a significant difference (p-value .002), in modes of deliveries. No significant association was observed in maternal and fetal complications like PPH, endometritis, and low Apgar score <7 in five minutes. The majority of neonates admitted for observation at the care unit. The neonatal mortality was two. Conclusions: Caesarean mode of delivery highly was associated with labor induction due to induction failure and fetal distress. Carefully selected cases improve morbidity and fetomaternal outcomes following labor induction.